Beyond individualism - Piore, Michael J. 1940- (Harvard Univ. Press, 1995)
Piore traces our difficulties in addressing these issues to the limits of liberal social theory, particularly its sharp distinctions between individuality and community. He offers an alternative view of individuality as emerging through the discussions and debates conducted among a community's members. These discussions, Piore suggests, have turned inward, away from the borderlands where social groups and economic organizations meet - and therein lies the crux of some of the country's deepest political and economic problems. His book points beyond the liberal conception of politics as a negotiation among competing interests and of policymaking as technical decisionmaking. Instead, it prescribes a politics focused on the process of discussion and debate itself, a politics that enlarges the borderlands by broadening the range of people who talk to one another and the range of topics they address